Histoplasmose pulmonar grave em um gato doméstico: tratamento com Anfotericina B e Itraconazol - Jardim, Mariana Palha de Brito; da Silva, Monique Lourenço; de Jesus, Amanda Chaves; Cid, Gabriela de Carvalho; Damico, Cristiane Brandão; dos Santos, Carla Regina Gomes Rodrigues; de Souza, Heloisa Justen Moreira (Acta Scientiae Veterinariae, 2018)
Background: Histoplasmosis is a systemic mycosis whose etiologic agent is the fungus Histoplasma capsulatum. This fungal infection, which is the second most frequent systemic mycotic fungal disease in felines in the United States, has rarely been found in cats in Brazil. This paper reports on a case of acute pulmonary histoplasmosis in a domestic cat treated with oral itraconazole associated with amphotericin B administered subcutaneously. This treatment resulted in clinical remission of the patient’s symptoms, as evidenced by radiographic follow-ups. Case: A domestic cat suffering from acute dyspnea was taken to a veterinary clinic. The animal was subjected to emergency oxygen therapy, and kept at rest through sedation with midazolam. A physical examination revealed normally colored mucosa, 8% dehydration, bristly fur, body condition score 2/9, tachypnea with respiratory rate of 100 breaths per minute and expiratory dyspnea. The radiographic examination showed marked opacification of all the pulmonary fields, with a mixed pattern (interstitial and alveolar) of heterogeneous appearance and diffuse distribution, which are changes consistent with an inflammatory infectious process (pneumonia). A cytological analysis of the pleural fluid revealed round to oval-shaped intracytoplasmic structures, varying in size from 2 to 4 μm, inside foamy macrophages, consistent with Histoplasma capsulatum. Based on the diagnosis of pulmonary histoplasmosis, and in view of the patient’s acute respiratory distress, it was decided to treat the cat using itraconazole associated with amphotericin B. Itraconazole was administered orally at a dose of 100 mg/cat every 24 h, while amphotericin B was administered subcutaneously at a dose of 0.5 mg/kg, combined with 100 mL of sodium chloride 0.9% and 100 mL of 5% glycated serum, with monitoring of serum concentrations of symmetric dimethylarginine (SDMA). Amphotericin B was administered every 48 h up to the 7th dose, followed by three times a week up to the 11th dose, and then twice a week up to the 16th dose. The animal was released from the veterinary hospital 10 days after its admission, showing a considerably improved respiratory condition and a respiratory rate of 40 breaths per minute. Continuation of the antifungal treatment with itraconazole was prescribed, maintaining the same dose and frequency of administration until a new recommendation would be made, as well as frequent return visits for the administration of amphotericin B and reassessment of the animal. The administration of amphotericin B was discontinued when the animal’s respiratory condition stabilized; hence, the feline received a total of 16 doses of the drug. The animal showed remission of clinical respiratory symptoms, confirmed by follow-up chest X-rays, which revealed significantly less radiodense pulmonary parenchyma in response to treatment with itraconazole and amphotericin B. Five months after beginning its treatment, the cat is being treated orally with itraconazole (100 mg/cat, every 24 h), without recrudescence of the clinical symptoms. Discussion: To date, six cases of feline histoplasmosis have been reported in Brazil, only one of which had pulmonary involvement and was treated successfully. The use of oral itraconazole associated with subcutaneous amphotericin B has proved to be effective for the treatment of acute pulmonary histoplasmosis in domestic cats. Note that a rapid diagnosis of pulmonary disease is essential in order to immediately implement a combined drug therapy linked with monitoring to ensure the protocol is safe for the patient